Parental Responsibility and Children Protection: The 1996 Hague Convention vs. the 1993 Minsk Convention - ABASHIDZE, Aslan; GUGUNSKIY, Denis; KEBURIA, Kristina; KONEVA, Aleksandra; SOLNTSEV, Alexander (Journal of Advanced Research in Law and Economics, 2018)
The article analyses comparatively universal and regional mechanisms, aimed at children`s rights protection, namely, the 1996 Hague Convention and the 1993 Minsk Convention (CIS). Both legal instruments create measures for the children`s best interests protection in international or cross-border conflicts between the parents, including such issues as recognition and enforcement of judgments concerning the children made by the competent judicial (primarily) and administrative authorities of one of the Member State within the territory of another. This article argues that the 1996 Hague Convention has a wider range of opportunities to protect the children`s rights, than the 1993 Minsk Convention. However, 1993 Minsk Convention remains important as most of the CIS Member States are not yet Contracting Parties to the 1996 Hague Convention. Russia, however, is a Contracting Party to both these Conventions although it has two separate Authorities to apply them. In cases falling within either Convention, it is argues that the Russian competent authorities should apply, as per 1996 Vienna Convention on the Law of Treaties the ‘later treaty’.